From Challenges to Solutions: Policy Driven and Technological Pathways Toward Sustainable Waste Management in Developing Countries - Maulia, Jihan Tasyabitah Tri (Jurnal Riset Kualitatif dan Promosi Kesehatan, 2023)
Effective waste management is crucial for maintaining environmental health and sustainability. This study examines the key challenges and potential solutions in waste management, particularly in developing regions, where inadequate infrastructure, weak regulations, and low public awareness contribute to environmental degradation. Using a systematic literature review, data from peer reviewed sources were analyzed to identify prevailing waste management issues and strategies. The findings indicate that ineffective waste policies and limited technological integration exacerbate waste related challenges, leading to increased pollution and public health risks. Emerging solutions, including the adoption of IoT based waste tracking systems, advanced recycling technologies, and policy driven economic incentives, show promise in enhancing waste management efficiency. The study underscores the need for a collaborative approach involving governments, industries, and communities to achieve sustainable waste management. The implications of this research suggest that strengthening regulations, investing in infrastructure, and promoting public education on waste reduction are essential steps toward sustainability. Future research should explore the long term impact of waste management strategies and assess cross regional policy implementations. By integrating technology and policy reforms, waste management can contribute significantly to environmental conservation and improved public health outcomes